Pengaruh Manfaat dan Resiko Terhadap Minat Penggunaan E-Wallet DANA di UINSU - Syifa Alhusna; Yenni Samri Juliati Nasution; Nurwani Nurwani (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This study aims to determine the effect of benefits and risks on interest in using E-Wallet DANA at UINSU partially and simultaneously. The type of research used is quantitative research with questionnaire data collection techniques and a population of 1125 students of the Sharia Accounting Study Program at the State Islamic University of North Sumatra with a sample used of 92 respondents with sampling techniques using purposive sampling. Data testing techniques used in this study include Descriptive Statistical Analysis, Validity Test and Reliability Test, Classical Assumption Test, Multiple Linear Regression Test, t test, F test, and Determination Coefficient Test. The results of this study indicate that First, the Benefits variable has a positive and significant effect on Interest with a t value (2.399) > t table (1.662). Second, Risk has a negative and significant effect on Interest with a calculated t value (- 1.029) < t table (1.662) and a significant value of 0.000 < 0.05. Third, the Benefits and Risk Variables affect the Interest in using e-wallets simultaneously (together), with Fcount> Ftable (11.199> 3.10) and a sig value of 0.000 <0.05.